Large vessel occlusion stroke outcomes in diabetic vs. non-diabetic patients with acute stress hyperglycemia - Duan, Honglian; Yun, Ho Jun; Rajah, Gary Benjamin; Che, Fengli; Wang, Yanling; Liu, Jing; Tong, Yanna; Cheng, Zhe; Cai, Lipeng; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neuroscience, 2023)
Objective This study assesses whether stress-induced hyperglycemia is a predictor of poor outcome at 3 months for patients with acute ischemic stroke (AIS) treated by endovascular treatment (EVT) and impacted by their previous blood glucose status. Methods This retrospective study collected data from 576 patients with AIS due to large vessel occlusion (LVO) treated by EVT from March 2019 to June 2022. The sample was composed of 230 and 346 patients with and without diabetes mellitus (DM), respectively, based on their premorbid diabetic status. Prognosis was assessed with modified Rankin Scale (mRS) at 3-month after AIS. Poor prognosis was defined as mRS>2. Stress-induced hyperglycemia was assessed by fasting glucose-to-glycated hemoglobin ratio (GAR). Each group was stratified into four groups by quartiles of GAR (Q1–Q4). Binary logistic regression analysis was used to identify relationship between different GAR quartiles and clinical outcome after EVT. Results In DM group, a poor prognosis was seen in 122 (53%) patients and GAR level was 1.27 ± 0.44. These variables were higher than non-DM group and the differences were statistically significant (p < 0.05, respectively). Patients with severe stress-induced hyperglycemia demonstrated greater incidence of 3-month poor prognosis (DM: Q1, 39.7%; Q2, 45.6%; Q3, 58.6%; Q4, 68.4%; p = 0.009. Non-DM: Q1, 31%; Q2, 32.6%; Q3, 42.5%; Q4, 64%; p < 0.001). However, the highest quartile of GAR was independently associated with poor prognosis at 3 months (OR 3.39, 95% CI 1.66–6.96, p = 0.001), compared to the lowest quartile in non-DM patients after logistic regression. This association was not observed from DM patients. Conclusion The outcome of patients with acute LVO stroke treated with EVT appears to be influenced by premorbid diabetes status. However, the poor prognosis at 3-month in patients with DM is not independently correlated with stress-induced hyperglycemia. This could be due to the long-term damage of persistent hyperglycemia and diabetic patients’ adaptive response to stress following acute ischemic damage to the brain.